New Records of Egg Parasitoids of Stink Bugs (Hemiptera: Pentatomidae) on Rice in Piauí, Brazil: Rate Parasitism, Incidence and Seasonality - Silva, Nadja N. P.; Sousa, Kátia K. A.; Silva, Paulo Henrique S.; Querino, Ranyse B. (Entomological Communications, 2021)
This study was conducted to investigate parasitism of naturally occurring pentatomid eggs in rice crops in a Cerrado-Caatinga ecosystem during the rainy and dry seasons in Teresina, Piauí, Brazil. Also, it provides information on the incidence and seasonality of parasitoid species. Parasitism was registered only during the rainy season, where Telenomus podisi (Ashmead, 1893) parasitized Oebalus poecilus (Dallas, 1851), Tibraca limbativentris (Stal, 1860) and Euschistus heros (Fabricius, 1798) eggs. Additionally, Trissolcus urichi (Crawford, 1913) was collected from O. poecilus and T. limbativentris eggs. Ooencyrtus anasae (Ashmead, 1887) was found in O. poecilus eggs. Such findings provide information that can be used to supplement the management of pentatomid pests in the rice agroecosystems, in Piauí, Brazil.